2003
DOI: 10.1073/pnas.0932698100
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a fusion kinase in EOL-1 cells and idiopathic hypereosinophilic syndrome

Abstract: Idiopathic hypereosinophilic syndrome (HES) is a myeloproliferative disease of unknown etiology. Recently, it has been reported that imatinib mesylate (Gleevec), an inhibitor of Bcr-Abl kinase useful in the treatment of chronic myeloid leukemia, is also effective in treating HES; however, the molecular target of imatinib in HES is unknown. This report identifies a genetic rearrangement in the eosinophilic cell line EOL-1 that results in the expression of a fusion protein comprising an N-terminal region encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(146 citation statements)
references
References 27 publications
2
141
0
3
Order By: Relevance
“…10 The majority of these imatinib-responders with HES were ultimately found to have an interstitial deletion in chromosome 4q12 causing the constitutively active fusion tyrosine kinase, FIP1L1-PDGFRA, which can be detected by FISH or reverse transcriptase-polymerase chain reaction (RT-PCR) in peripheral blood or bone marrow. 7,18 Many other imatinib-sensitive PDGFR fusions, including KIF5B-PDGFRA and ETV6-PDGFRB, 19-21 and point mutations in PDGFRA 22 have been described in patients presenting with clinical features of HES, but are uncommon.…”
Section: Myeloproliferative He/hes (M-he or M-hes; He Or Hes With Docmentioning
confidence: 99%
“…10 The majority of these imatinib-responders with HES were ultimately found to have an interstitial deletion in chromosome 4q12 causing the constitutively active fusion tyrosine kinase, FIP1L1-PDGFRA, which can be detected by FISH or reverse transcriptase-polymerase chain reaction (RT-PCR) in peripheral blood or bone marrow. 7,18 Many other imatinib-sensitive PDGFR fusions, including KIF5B-PDGFRA and ETV6-PDGFRB, 19-21 and point mutations in PDGFRA 22 have been described in patients presenting with clinical features of HES, but are uncommon.…”
Section: Myeloproliferative He/hes (M-he or M-hes; He Or Hes With Docmentioning
confidence: 99%
“…In the case of PDGFRA fusions, both the BCR-PDGFRA 16,17 and FIP1L1-PDGFRA 8,18 fusions were identified in 2002-2003 as recurrent rearrangements, with the FIP1L1-PDGFRA fusion being the most common fusion. A few other variant PDGFRA fusion genes have now also been described (Table 3).…”
Section: Terminology and Classificationmentioning
confidence: 99%
“…The essential role of FIP1L1-PDGFRA is clear from in vitro studies with the EOL-1 cell line, from mouse models of FIP1L1-PDGFRA induced disease, and from the remarkable responses of FIP1L1-PDFGRA-positive CEL patients to imatinib treatment. 8,18,65,66 The mouse model, however, has also suggested that expression of the FIP1L1-PDGFRA fusion is most likely not sufficient to cause eosinophilia, as mice expressing FIP1L1-PDGFRA in their bone marrow cells develop a general myeloproliferative disease without eosinophilia. 65 Expression of FIP1L1-PDGFRA together with overexpression of IL-5, however, mimics the disease much better in the mouse, with typical features of HES such as tissue infiltration of eosinophils.…”
Section: Role Of Fip1l1mentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation of the ability of imatinib mesylate to treat HES patients revealed the existence of an 800 kilobase deletion in chromosome 4 bringing together an upstream DNA sequence homologous to a yeast protein, referred to as FIP1, and designated as like FIP1, or FIP1-L1 and the gene for the cytoplasmic domain of the platelet derived growth factor alpha (PDGFRA) receptor. [65,70] This fusion gene is transcribed and translated yielding a novel kinase referred to as FIP-L1-PDGFRA; FIP-L1-PDGFRA is exquisitely sensitive to imatinib in vitro, thus explaining the remarkable sensitivity of HES patients to this drug. The FIP-L1-PDGFRA fusion gene cooperates with IL-5 overexpression in a murine model of HES, suggesting that both pathogenic events cooperate in disease etiology.…”
Section: Gastrointestinal Eosinophilia In Hypereosinophilic Syndrome mentioning
confidence: 99%